THE EFFECT OF SELF-REGULATED LEARNING AND DIGITAL LITERACY ON STUDENTS ECONOMIC LEARNING OUTCOMES WITH SELF-EFFICACY AS AN INTERVENING VARIABLE - Adia Maritza Adha; Ari Saptono; Siti Fatimah Zahra (Yayasan Education and Social Center, 2022)
During the Covid-19 pandemic, all learning activities in school will carry out at home. All aspects of education require adaptation to this policy, and the most affected by this policy are students. Students learning outcomes at SMA Negeri 8 Tangerang Selatan have decreased, as seen from the PAS (Penilaian Akhir Semester) scores of students for the 2021/2022 academic year in the odd semester. It found that 80 percent of students with PAS scores were still below the minimum completeness criteria (KKM). One way to overcome this the students must apply self-regulated learning and self-efficacy strategies during the online learning process. In addition, students also need to adapt to technology which students' digital literacy skills can measure by using technology. This study aims to determine the effect of self-regulated learning and digital literacy on students' economic learning outcomes with self-efficacy as an intervening variable. The population of this study is class XI students in the 2021/2022 academic year at SMAN 4 Tangerang Selatan and SMAN 8 Tangerang Selatan, with a total of 305 students. Sampling obtains using the slovin formula with a total sample of this study are 174 students. Techniques for collecting data using questionnaires and methods for analyzing data using path analysis with the IBM SPSS 25.0 program describe here. Self-efficacy is an intervening variable, and the results showed a positive and significant influence between self-regulated learning and digital literacy on students' economic learning outcomes